A Quantitative Cross-Regional Analysis of the Spanish VET Systems From a Systemic Approach: From a Regional Comparative VET Research Perspective - Monica Moso-Diez; Antonio Mondaca-Soto; Juan P. Gamboa; Mikel Albizu-Echevarría (European Research Network Vocational Education and Training (VETNET), 2022)
Purpose: The aim of this paper is to analyse comparatively, at regional level, the current state of a wide range of indicators of Vocational Education and Training (VET) at regional level in Spain. This will make it possible to characterise and better understand the existence of a variety of regional VET systems, including the Initial VET and Continuous VET subsystems within Spain, doing so under a multidimensional approach examining VET supply and demand. Methods: Systemic analysis of Spanish VET indicators leads to a selection of 54 indicators, which are then compared at regional level using k-means clustering. This approach identifies similarities and differences (clusters) across all of Spain's 17 autonomous communities (Spanish regions). The correlation between the variables is then analysed to examine the interaction between the VET system's supply and demand dimensions. Findings: The results show that 19 indicators explain the main differences between autonomous communities, which form two distinct clusters. Both VET supply and VET environment and demand influence cluster formation and inter-cluster differences. In the set of indicators that differentiate the two clusters of autonomous communities, close interaction is detected between certain indicators of VET supply and demand, especially those referring to the STEM occupational group, which confirms the correlation between these dimensions, albeit to a limited extent.  Conclusions: While it is necessary to analyse the differences between clusters in greater depth, the results suggest that Spain's regions are split into two distinct groups (clusters) in which the respective VET systems are developing and advancing differently. Moreover, there is evidence of a small number of significant interrelations between indicators of VET supply and demand, which point to both the VET system's specialisation and its inclusive nature.